Left Brain, Right Brain: Facts and Fantasies - Corballis, Michael C. (PLOS Biology, 2014)
Michael Corballis discusses in this essay how the asymmetry of the brain raises questions about genetics, evolution, language, and educational and psychological disabilities; but beware of exaggerated claims of left brain/right brain polarities.